Substance for the prevention and treatment of early stage of caries based on vegetable raw materials (Experimental biology, 2015)
The using of regional plant raw materials for the effective prophylaxis of teeth caries was proposed. The next pharmacokinetic groups with different mechanisms of acting were distinguished: 1) improvement of gums’ bloodcirculation and the metabolism in the soft tissue; 2) regulation of the quantity of pathogenic and conditionally pathogenicmicro flora in the oral cavity; 3) regulation of the viscosity and increasing of defending properties of saliva; 4) keeping of biogenic Fluor or Calcium; 5) keeping of siliceous compounds; 6) keeping of complex of micro-elements positively influencing to the metabolism in the teeth hard tissues; 7) mummification of pulp and other necrotized soft tissues on pulp and periodontal inflammation; 8) improving of digestive tract and correction of metabolism in the organisms of people or animals. Authors elaborated and patented medicine mean for the caries prophylaxis and improving ofhygienic condition of oral cavity from regional herbal raw materials.
Keywords: caries; mineral teeth tissue; re-mineralization; plant raw materials; pharmacokinetic; protective properties of saliva; silicates